Transformasi Penghimpunan Dana Wakaf Di Era Digital - Yanti, Juli Darma; Rozalinda, Rozalinda; Ikhsan, Ainul (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2025)
Waqf is one type of Islamic philanthropy already There has been since a long time ago. It's used for service education, social, agriculture, and health as well as objective religious. Study This aims to investigate how the transformation of waqf in the digital era can increase efficiency as well as transparency in the management of waqf funds carried out by the Indonesian Waqf Board. On research This use studies bibliography. primary data is data sources used in research This ie in a way direct from journal journall related to transformation digital and collected waqf through descriptive. Research results disclose that BWI continues to endeavor to transform in collecting waqf funds, which includes three stages: strengthening digitalization in BWI, strengthening digitalization nazir and combination information waqf as well as speeding up strengthening environment computerization and creating a waqf model imaginative progress for executives. Theoretically, this study expands scientific understanding in the field of Islamic philanthropy and economics, particularly in relation to the digital revolution in waqf fund collection. The findings of this study can also serve as a guide for future research on innovation and the application of digital technology in waqf management.